Sustainable water filtration system - hybrid SRWaFilS: a low-cost and highly efficient system (rainwater-greywater collection and filtration unit) for non-potable use. - Muhamad Bashar, Nur Azwa; Ahmed, Ruziah; Abdul Kadir, Zuraini; Husnul Amir, Nur Alani Fatini; Husnul Amir, Nur Nisrina Nabihah; Mohd Hafiz, Muhamad Izz Rayyan; Mohd Khairani, Zara Khayr (Unit Penerbitan PKAPP, 2025)
For decades, global warming due to climate change has had an impact on society, the economy and the sustainability of the planet. Large areas of natural forests and land have been replaced with concrete and paved surfaces. These changes affect hydrometeorological conditions, leading to more extreme rainfall patterns, higher rainfall intensity, and flash floods caused by excessive surface runoff. This surface runoff is not absorbed by the soil system or intercepted by the drainage system due to certain factors such as the full capacity of the soil system (wet and saturated conditions), inadequate drainage capacity, and the absence of gutter systems in some residential areas (particularly older residential areas lacking sustainable rainwater harvesting systems). A clean and continuous water supply is compulsory for our daily life and activities. Conventionally, water stored in underground sources and reservoirs is treated before being supplied to consumers. Furthermore, the consumption of clean water before the above parameters listed by the World Health Organisation (WHO) and the specific water quality standards for each country is essential. In Malaysia, the water quality parameters must meet the National Water Quality Standard (NWQS) before the water can be used for both potable and non-potable use. The accumulation of rainwater has increased, especially during episodes of heavy rainfall caused by climate change, yet it is often neglected and left unused or untreated. This abundant rainwater can be collected, treated, and used for non-potable purposes such as cleaning pavements and watering gardens. Collecting rainwater from rooftops offers an effective solution to water scarcity, particularly in drought-prone and seasonally dry regions, as well as areas with high irrigation demands. In addition, the increasing volume of greywater from kitchen sinks and external drainage systems (canalised domestic water systems) can also be reused as service water. Even when the collected water is intended for non-potable purposes, it should still be treated to reduce chemical properties to levels deemed safe by the relevant authorities. If the collected rainwater is contaminated, physical contact with the water may cause adverse effects, such as skin redness or irritation. To address this, a portable and sustainable water filtration system is recommended for domestic use (both households and institutions). Such systems should be cost-effective, provide basic treatment of service water, and require minimal maintenance.